Communication skills Edition for University and College Students - Maina, Samuel Mwituria; Worth, Richard (Mwituria Publishers Nairobi, 2014)
"Knowing how to communicate clearly and effectively in the workplace is one of the keys to career success. Communication Skills, Third Edition focuses on the importance of solid speaking, writing, listening, and conversational skills for thriving in the workplace."--Amazon.com.
Writing with a purpose -- Speaking with confidence -- Communicating effectively -- Good communicators are good listeners -- Making meetings work.
Includes bibliographical references (p. [160]-164) and index.
013-017.
Keywords: Business communication -- Juvenile literature; Commercial correspondence -- Juvenile literature; Public speaking -- Juvenile literature; Listening -- Juvenile literature; Business communication; Commercial correspondence; Public speaking; Listening